2020
DOI: 10.1111/are.14777
|View full text |Cite
|
Sign up to set email alerts
|

Dietary curcumin supplementation enhanced growth performance, intestinal digestion, and absorption and amino acid transportation abilities in on‐growing grass carp ( Ctenopharyngodon idella )

Abstract: This study investigated the effect of curcumin on growth performance, intestinal digestion, and absorption and amino acid transportation in on‐growing grass carp (Ctenopharyngodon idella). Curcumin at six levels (control (0), 120, 240, 360, 480 and 600 mg/kg) was included in the fish diets for 60 days. Dietary curcumin supplementation increased weight gain, final body weight, body length, percentage weight gain, specific growth rate, feed intake, feed efficiency, intestinal somatic index, intestinal protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 70 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Intestinal stem cells continuously undergo self-renewal and give rise to the transit of cells that move up the crypt villi axis that form various differentiated cell types to maintain intestinal epithelial integrity [ 31 ]. Further, growth performance depends on the digestive and absorptive capacity of fish, especially in metabolism and nutrient absorption [ 32 ]. For example, dietary dandelion improved intestinal morphology and immunity by increasing the number of intestinal cupped cells and decreasing the number of epithelial lymphocytes in the pompano fish Trachinotus ovatus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal stem cells continuously undergo self-renewal and give rise to the transit of cells that move up the crypt villi axis that form various differentiated cell types to maintain intestinal epithelial integrity [ 31 ]. Further, growth performance depends on the digestive and absorptive capacity of fish, especially in metabolism and nutrient absorption [ 32 ]. For example, dietary dandelion improved intestinal morphology and immunity by increasing the number of intestinal cupped cells and decreasing the number of epithelial lymphocytes in the pompano fish Trachinotus ovatus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the multitude of pathways that curcumin can act on, it is challenging to identify the key pattern of action of this antioxidant. In fact, the impact of curcumin in the redox status of fish is highly dependent on the duration of the experimental trial [ 52 ], doses [ 10 , 15 ], and species [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Amirkhani and Firouzbakhsh [15] revealed that a 400 mg/kg diet of the basil (Ocimum basilicum) ethanolic extract could improve the growth performance of the common carp (Cyprinus carpio). In addition, other phytobiotics that positively influenced aquaculture species growth performances are fenugreek seed meal [16], date palm (Phoenix dactylifera) seed extract [17], Chlorella [18], juniper berry oil [19], white button mushroom powder [20], curcumin [21], and wheat meal [14]. Moreover, certain phytobiotics such as fenugreek seed meal exhibited additional benefits by reducing stress and improving growth performance [16].…”
Section: The Role Of Phytobiotics In Improving Carp Growth Performancementioning
confidence: 99%
“…Phytobiotic application improves nutrient availability and digestibility, contributing to enhanced feed conversion and protein synthesis [7]. Various phytobiotics like oregano essential oil [40], curcumin [21], grape pomace flour (GPF) [34], and savory (Satureja hortensis) essential oil [38] are easily applicable in carp farming as shown in Table 2. Nevertheless, these phytobiotics are only useful when the aquaculture species nutritional requirements are fulfilled.…”
Section: The Role Of Phytobiotics In Promoting Carp Feed Utilization ...mentioning
confidence: 99%